Mở rộng :v
\(4x^2-3x-504=0\)
\(\Delta=9+8064=8073>0\)
\(\Rightarrow\left\{{}\begin{matrix}x_1=\dfrac{3+\sqrt{8073}}{8}\\x_2=\dfrac{3-\sqrt{8073}}{8}\end{matrix}\right.\)
\(4x^2-3x-504=0\)
\(\Leftrightarrow4\left(x^2-\dfrac{3}{4}x-126\right)=0\)
\(\Leftrightarrow4\left(x^2-2.x.\dfrac{3}{8}+\dfrac{9}{64}-\dfrac{8073}{64}\right)=0\)
\(\Leftrightarrow4\left(x-\dfrac{3}{8}\right)^2-\dfrac{8073}{16}=0\)
\(\Leftrightarrow\left(x-\dfrac{3}{8}\right)^2=\dfrac{8073}{64}\)
\(\Leftrightarrow\left[{}\begin{matrix}x-\dfrac{3}{8}=\sqrt{\dfrac{8073}{64}}\\x-\dfrac{3}{8}=-\sqrt{\dfrac{8073}{64}}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3+3\sqrt{897}}{8}\\x=\dfrac{3-3\sqrt{897}}{8}\end{matrix}\right.\)